Factors Influencing Wus in the Selection of IUD Contraceptives at the Glugur Darat Health Center, East Medan District, Medan City - Simbolon, Rona Elisi Marcia; Nadapdap, Thomson Parluhutan; Lumbanraja, Sarma (Universitas Ibn Khaldun Bogor, 2025)
The government's efforts to deal with the population growth rate in Indonesia Data World Health Organization (WHO) shows that users of implantable contraceptives around the world are still under injectable contraceptives, pills, condoms and IUDs, especially in developing countries. The Medan City Health Office in 2022 found that there were 16,968 active birth control participants, of which 1,846 IUD users were used. For the number of postpartum birth control participants, there were 1,008 people with 142 IUD users and 13% of birth control drop-outs. The purpose of the study was to find out the factors that affect WUS in the selection of IUD contraceptives at the Glugur Darat Health Center, East Medan District, Medan City. The design of this study uses a mixed method. The population in this study is all WUS in the Glugur Darat Health Center, East Medan District, Medan City, which is as many as 251 family planning acceptors, with a qualitative sample of 72 WUS, for a qualitative sample of 3 WUS, 1 midwife, 2 husbands. Data analysis uses univariate, bivariate and mulitivariate analysis. The results of the study showed that there was an influence of knowledge, attitude, husband support, parity, and the role of health workers on the selection of IUD contraceptives at the Glugur Darat Health Center, East Medan District, Medan City. While the most dominant factor is knowledge. The conclusion of this study is that there is an influence of knowledge, attitude, husband support, parity and the role of health workers on the selection of IUD contraceptives at the Glugur Darat Health Center, East Medan District, Medan City. It is recommended to the Health Center to increase IUD selection and build positive information about IUD use by involving village PLKB officers and involving birth control acceptors as an example to eliminate the concerns of pus mothers so far through counseling activities and direct interviews with family planning participants so that it is expected to increase the use of IUDs.